2019
DOI: 10.33642/ijbass.v5n12p2
|View full text |Cite
|
Sign up to set email alerts
|

Product Performance Satisfaction Level of Mutual Fund Investors

Abstract: Product performance satisfaction level can be referred to as the satisfaction level of mutual fund investors in terms of return, transparency, safety, liquidity, service quality, fund management and the overall performance of the mutual fund products. Here, the researcher attempted to analyze the satisfaction level of mutual fund investors concerning different funds/schemes opted by the investors. Based on these objectives seven parameters of satisfaction of mutual fund investors including the overall performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Hence, there is a negative relationship between MDs and acquirer returns. As maintained by several previous studies (e.g., Alfadhl & Alabdullah, 2016, 2018Thomas, 2019;Alabduallah, 2019;Alshali, Alhattali, & Ahmed, 2021;Kanaan-Jebna, 2014;Alabdullah, 2016c;Alfadhl & Alabdullah, 2016;Alabdullah et al, 2016;2018;Almashhadani., 2020;. Chou and Feng (2019) showed that having MDs is linked to more effective cash management, which helps shareholders directly.…”
Section: The Relationship Between Multiple Directorships and Cash Hol...supporting
confidence: 64%
“…Hence, there is a negative relationship between MDs and acquirer returns. As maintained by several previous studies (e.g., Alfadhl & Alabdullah, 2016, 2018Thomas, 2019;Alabduallah, 2019;Alshali, Alhattali, & Ahmed, 2021;Kanaan-Jebna, 2014;Alabdullah, 2016c;Alfadhl & Alabdullah, 2016;Alabdullah et al, 2016;2018;Almashhadani., 2020;. Chou and Feng (2019) showed that having MDs is linked to more effective cash management, which helps shareholders directly.…”
Section: The Relationship Between Multiple Directorships and Cash Hol...supporting
confidence: 64%